Correlation between coping mechanism and safety behavior in construction workers of fabrication division in a steel construction company - Widajati, Noeroel; Martiana, Tri; Mulyono, Mulyono (Folia Medica Indonesiana, 2017)
Unsafe act become the most cause of accidents. One of human factors causing accidents is work stress. The aim of this study was to analyze correlation between coping mechanism and safety behavior at workers of fabrication division in a steel construction company. The study was carried out with cross-sectional analytical observational methods. The study population was 200 workers of fabrication division in a steel construction company. By using simple random sampling method, the number of samples was 134 respondents. Data collection was performed by observation, interviews, and questionnaires. The independent variables were age, education level, K3 experience, coping mechanism, emotional focused coping, and problem focused coping, while the dependent variable was safety behavior. Intervariables correlation were tested by Chi-square test (α=0.05). Correlation between age and safety behavior was categorized on relation (p=0.016; r=0.301). Correlation between education level and safety behavior was not categorized on relation (p=0.260; r=0.315). Correlation between tenure and safety behavior was categorized on relation (p=0.001; r=0.422). Correlation between coping mechanism and safety behavior was not categorized on relation (p=1.0; r=0.015). The conclusion was age and tenure have unidirectional and strong relation with safety behavior, while the level of education and coping mechanism have no relation with safety behavior. Company should have given understanding to workers about safety behavior through K3 training and safety talk and held safety inspection and or safety patrol to supervise workers.